Pengaruh Sistem Jasa Titip dan Branding Melalui Tiktok terhadap Keputusan Pembelian Konsumen pada UKM Sop Buah Irine - Baiti Lailatul Maghfiroh; Sri Andayani; Ni Made Ida Pratiwi (Politeknik Kampar, 2025)
The product consignment system is a business model in which consumers order products through intermediaries, and intermediaries buy the products at a specific location and send them to end consumers. Branding through TikTok is a digital marketing strategy to build a brand image, product, or service on the social media TikTok. This study aims to analyze the influence of the product consignment system and branding through TikTok on consumer purchasing decisions in small and medium enterprises (SMEs) Sop Buah Irine. In the increasingly developing digital era, digital-based marketing strategies are key for SMEs to compete in the market. The product consignment system allows consumers to buy goods that are difficult to reach directly, while branding through TikTok functions to increase brand awareness and attract consumers' attention through viral creative content. The research method used is quantitative with a descriptive and explanatory research approach. Data were collected through questionnaires distributed to 100 respondents who were active TikTok users and had purchased Sop Buah Irine products. The results of the analysis show that both the consignment system and branding through TikTok have an influence on consumer purchasing decisions. Specifically, branding through TikTok has been shown to have a more dominant influence compared to the consignment system. This study provides insight for the owners of Irine Fruit Soup UKM to optimize their digital marketing strategies, as well as providing recommendations for further research to explore other variables that may influence consumer purchasing decisions.